PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG LISTING DI BURSA EFEK INDONESIA - Hamzah Fansuri; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to examine the persial and simultaneous influence of firm size, sales growth, and profitability of capital structure. Where independent variables in this study is the size of the company, sales growth, and profitability while the dependent variable is the capital structure. The sample used is secondary data derived from the financial statements of textile and garment companies listed on the Indonesia Stock Exchange (IDX) period 2009 to 2014. This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. The classical assumption test in this research includes normality test, multicollinearity test, heterokedastisity test and autocorrelation test. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 20. The results of this study indicate that firm size variables persial (t test) affect the capital structure, while the variable sales growth and profitability does not affect the capital structure of textile and garment companies listed on the Indonesia Stock Exchange. The simultaneous test results (f) show the significant effect of firm size variable, sales growth, and profitability on capital structure in textile and garment companies listed in Indonesia Stock Exchange. Keywords : Company size, sales growth, profitability, and capital structure